2023
DOI: 10.1111/iej.13901
|View full text |Cite
|
Sign up to set email alerts
|

Root filled teeth in two parallel Danish cohorts: A repeated longitudinal cohort study

Abstract: Aim The aim of the study was to compare the frequency of root filled teeth and quality of root fillings (RFs) in two parallel, Danish cohorts each examined over 10 years and to evaluate factors associated with apical periodontitis (AP) and extraction of root filled teeth. Methodology Two randomly selected cohorts (C1, C2) from Aarhus (age: 20–64 years) were followed for approximately 10 years, with full‐mouth radiographic surveys performed at 5‐year intervals (C1: 1997–2003–2008; C2: 2009–2014–2019). Frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 76 publications
2
7
0
Order By: Relevance
“…the descriptive analyses of individuals participating in the first, second, and third examinations indicated that the selection caused by drop-out during follow-up did not introduce serious bias for main findings regarding teeth with aP, root filled teeth, and tooth extractions in c1 and c2. a comparison of individuals, who participated in all three examinations, with those, who did not, showed that the individuals, who did not participate in all three examinations, were younger; but no differences in the number of root filled teeth per person and the proportion of root filled teeth with aP were found [12]. thus, the results based on individuals from c1 and c2, who participated in all three examinations, seem relevant.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…the descriptive analyses of individuals participating in the first, second, and third examinations indicated that the selection caused by drop-out during follow-up did not introduce serious bias for main findings regarding teeth with aP, root filled teeth, and tooth extractions in c1 and c2. a comparison of individuals, who participated in all three examinations, with those, who did not, showed that the individuals, who did not participate in all three examinations, were younger; but no differences in the number of root filled teeth per person and the proportion of root filled teeth with aP were found [12]. thus, the results based on individuals from c1 and c2, who participated in all three examinations, seem relevant.…”
Section: Discussionmentioning
confidence: 85%
“…in addition, the use of several observers necessitated a thorough calibration of the observers. this has been described and discussed in detail in previous articles [11,12].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations